Does coexisting accommodative dysfunction impact clinical convergence measures, symptoms and treatment success for symptomatic convergence insufficiency in children?. (3rd November 2021) - Kulp, Marjean T; Sinnott, Loraine T; Cotter, Susan A; Borsting, Eric; Toole, Andrew J; Chen, Angela M; Jenewein, Erin C; Morrison, Ann M; Plaumann, Maureen D; Jones‐Jordan, Lisa; Mitchell, G Lynn; Tea, Yin C; et al.
Abstract: Purpose: To determine whether coexisting accommodative dysfunction in children with symptomatic convergence insufficiency (CI) impacts presenting clinical convergence measures, symptoms and treatment success for CI. Methods: Secondary data analyses of monocular accommodative amplitude (AA; push‐up method), monocular accommodative facility (AF; ±2.00 D lens flippers) and symptoms (CI Symptom Survey [CISS]) in children with symptomatic CI from the Convergence Insufficiency Treatment Trial ( N = 218) and CITT‐Attention and Reading Trial ( N = 302) were conducted. Decreased AA was defined as more than 2D below the minimum expected amplitude for age (15 – ¼ age); those with AA < 5 D were excluded. Decreased AF was defined as <6 cycles per minute. Mean near point of convergence (NPC), near positive fusional vergence (PFV) and symptoms (CISS) were compared between those with and without accommodative dysfunction using analysis of variance and independent samples t‐testing. Logistic regression was used to compare the effect of baseline accommodative function on treatment success [defined using a composite of improvements in: (1) clinical convergence measures and symptoms (NPC, PFV and CISS scores) or (2) solely convergence measures (NPC and PFV)]. Results: Accommodative dysfunction was common in children with symptomatic CI (55% had decreased AA; 34% had decreased AF). NPC was significantly worse in those with decreased AA (mean difference = 6.1 cm; p < 0.001). Mean baseline CISS scores were slightly worse in children with coexisting accommodative dysfunction (decreased AA or AF) (30.2 points) than those with normal accommodation (26.9 points) (mean difference = 3.3 points; p < 0.001). Neither baseline accommodative function ( p ≥ 0.12 for all) nor interaction of baseline accommodative function and treatment ( p ≥ 0.50) were related to treatment success based on the two composite outcomes. Conclusions: A coexisting accommodative dysfunction in children with symptomatic CI is associated with worse NPC, but it does not impact the severity of symptoms in a clinically meaningful way. Concurrent accommodative dysfunction does not impact treatment response for CI.